PERBEDAAN PENGGUNAAN MEDIA POWERPOINT DAN VIDEO PEMBELAJARAN TERHADAP KEMAMPUAN BERPIKIR TINGKAT TINGGI DAN RETENSI MEMORI SISWA PADA MATA PELAJARAN IPA DI KELAS V SD - Suwisnawati Gowasa; Fauziyah Harahap; Retno Dwi Suyanti (JURNAL TEMATIK, 2019)
This study aims to compare: (1) High-level thinking skills and (2) Retention ofstudents' memory in respiratory system material in humans who are taught by usingpower point media and learning video media on respiratory system material in humans.This quasi-experimental study was conducted at SD RK No. 3 Sibolga City, with asample of 2 classes determined by cluster random sampling technique. The results of thestudy showed: (1) the high-level thinking skills of students who were taught with learningvideo media were better than students who were taught with power point media (63.06:56.96) which were significantly statistically significant (t = 2.100; p = 0.040), likewise(2) memory retention of students taught with learning video media is better than studentstaught with power point media (83.28: 78.03) which is significantly different (t = 2.728; p= 0.008 ) It is expected that the teacher can use learning video media in the material ofhuman respiratory system in an effort to improve students 'high-level thinking skills andstudents' natural science memory retention.